Towards a smarter globe - the smart partnership way for realising socio-economic transformation through regional integration : smart partners' insights ([s.n.] [S.l.], 2009)
Reports on deliberations centered on achieving transformation through inclusivity in national visions and regional integration
Keywords: ECONOMIC CHANGE